Rozwój ochrony przeciwpożarowej na ziemi lubuskiej w latach 1945-1949 = Ziemia lubuska's firemen of 1945-1949: more than fire fighters - Koteluk, Daniel (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
After the end of World War II, the firemen and some other settlers, arriving in ziemia lubuska, managed to set up an effective fire fighting force - despite their insufficient numbers and lacking equipment. Over the period of 1945-1949 they helped the local people put out numerous fires in the region. Besides, they organized culture and education events for the village folk.
Keywords: Ochotnicza Straż Pożarna; Ziemia Lubuska; historia - 1945-1989